ANXIETY AND DEPRESSIVE DISORDERS IN RHEUMATOID ARTHRITIS: A CLINICAL PSYCHIATRIC STUDY - Urolova D.A.; Gopurova G.F. (Central Asian Journal of Medicine, 2025)
Studies show that patients with rheumatic disease usually have the following anxiety-depressive spectrum disorders: depressive episodes (single and recurrent) of varying severity with concomitant anxiety; dysthymia (chronic depression of moderate severity); generalized anxiety disorder, as well as adjustment disorders with anxiety and depressive symptoms.